Dominasi Media Konvensional dan Implikasinya terhadap Produksi Ujaran Pemelajar BIPA Level 4: Analisis Berbasis Pendekatan Komunikatif - Lintang Putri Pratiwi; Anas Ahmadi; Agusniar Dian Savitri (Paedagogie, 2026)
The purpose of this study is to describe the conditions of using learning media in BIPA level 4 classes and analyze its suitability with the principles of communicative approach in encouraging the production of learners' speech. The researcher uses a descriptive qualitative approach with a case study design. Data collection was carried out through passive participatory observation (seat-in), documentation, and unstructured interviews with BIPA teachers. The collected data was analyzed using an interactive analysis model that included the stages of data reduction, data presentation, and conclusion drawn, and its validity was guaranteed through source triangulation and technical triangulation. The results of the study show that the learning media used is still dominated by Microsoft PowerPoint which is conventional and has not been systematically integrated in the learning design. Four inconsistencies were found with the principle of the communicative approach, namely that the media has not been able to present an authentic communication situation, interaction between learners is not facilitated in a planned manner, cultural integration in the media has not been optimal, and the initiation of speaking independently is only observed in one in four learners. The conclusion of this study emphasizes that the dominance of conventional media has an impact on the limited space for the production of meaningful speech for BIPA level 4 learners, so that more communicative, contextual, and culture-based media innovations are needed in advanced BIPA learning.